A 10-year ecological study of the methods of suicide used by Brazilian adolescents - Denisse Claudia Jaen-Varas; Jair J. Mari; Elson Asevedo; Rohan Borschmann; Elton Diniz; Carolina Ziebold; Ary Gadelha (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: Suicide among adolescents has become a major public health problem worldwide. Our study sought to describe the most commonly used methods of suicide among adolescents aged 10 to 19 years in Brazil between 2006 and 2015. Complete data were obtained from the Brazilian Health Informatics Department (DATASUS) and coded into seven categories of suicide methods. The following statistical analyzes were performed: chi-square (χ2) tests to examine the association between the frequency of each suicide method and the year; odds ratios (OR) and 95% confidence intervals (95%CI) compared the relative chances of each suicide method occurring between boys and girls. In total, 8,026 suicides among Brazilian adolescents were registered over the analyzed period. The most commonly used method of suicide by both sexes was hanging (2015 = 70.3%), and the most significant increase was observed in girls (2015 = 65.82%). The proportional use of arms (2006 = 14.2%; 2015 = 9.1%) and poisoning (2006 = 13.3%; 2015 = 9.2%) decreased over the period. The increase in hanging is worrisome, mostly due to difficulties to impose access barriers and to its high lethality. In such context, a comprehensive understanding of suicide behaviors among adolescents in Brazil should be drawn to inform general prevention measures and, more specifically, the reasons for the increase in hanging need to be further investigated.